Proti meticilinu odporna bakterija Staphylococcus aureus domačega okolja (CA-MRSA) - Grmek-Košnik, Irena (Zdravniški vestnik, 2005)
Background. Community acquired MRSA (CA-MRSA) infections affect patients without risk factors. CA-MRSA infections can be serious and also fatal even inpreviously healthy subjects. CA-MRSA differs from hospital acquired MRSA (HA-MRSA). CA-MRSA is more susceptible for non-beta-lactam antibiotics than HA-MRSA, has different PFGE subtypes, and can produce Panton-Valentine leukocidine. Methods. In Institute of Public Health Kranj we routinely performepidemiologic survey of MRSA positive patients. We compared MRSA isolates from patients with and without risk factors for acquisition of MRSA. We tested all S. aureus for their susceptibility to antibiotics (penicillin, oxacillin, vancomycin, gentamicin, erythromycin, clindamycin, tetracycline, cipro floxacine, chloramphenicol, trimethoprim sulfamethoxazole and rifampin).All CA-MRSA isolates were tested for susceptibility to fusidic acid staphylococcal enterotoxin (SE) production. We performed macrorestriction chromosome analysis with pulse field gel electrophoresis (PFGE). We compared CA-MRSA characteristics with epidemic MRSA strains. Results. In the period from 1999 to 2004 we isolated 1439 MRSA including 10 isolates suspicious for CA-MRSA. This isolates were susceptible for more than 5 antibiotics in contrast to epidemic MRSA which were susceptible for 3 or S antibiotics. Eightof 10 CA IVIRSA produced SE C or D or no SE, in contrast to epidemic MRSA, which produced exclusively SE A. In PFGE CA-MRSA showed different patterns compared to epidemic HA-MRSA. Conclusions. With exclusion of risk factors for MRSA acquisition in patient's history testing for antibiotic susceptibility, SE production and PFGE we proved that our MRSA isolates differed from ordinary epidemic strains. We identified CA-MRSA also in Slovenia.
Keywords: antibiotic; Antibiotics; Antibiotiki; bacteria; bakterije; Community-Acquired Infections; Electrophoresis, Gel, Pulsed-Field; Elektroforeza gelska, pulzirajoče-polje; Infekcije, domačega okolja; Methicillin Resistance; Meticilinska rezistenca; Microbial Sensitivity Tests; Mikrobni, občutljivostni testi; odpornost; stafilokoki; Stafilokokne infekcije; Staphylococcal Infections; Staphylococcus Aureus